Spectra of subnormal pairs - Rudol, Krzysztof (My University, 2007)
In this short note we present an example related to joint spectra of subnormal pairs of bounded operators. A counterexample to the equality between Taylor's spectrum and the closure of the defect spectrum is given. This example is related to the author's modification of N Sibony's counterexample to Corona Theorem on domains that fail to be strictly pseudoconvex.
Opuscula Mathematica
Keywords: subnormal operator; corona; joint spectrum